(untitled) (Global Business Management Review (GBMR), 2018)
The study examined the impact of post-financial crisis stress test results announcements on stock return of DMBs in Nigeria over a thirty-One (31) days event window and one hundred (100) days estimation window, for the period June 2013 to June 2016. The secondary data used in the study was analyzed using event study methodology for a sample of 15 DMBs drawn from population of twenty-two DMBs in Nigeria. The residuals of abnormal returns over the event window were subjected to diagnostic tests for serial correlation, normality and heteroskedasticity, the results indicated that the model was correctly specified. The result of test of hypotheses indicated that there is no significant CAR before, on the days and after post crisis stress test results announcements on stock returns of DMBs in Nigeria. Thus, the study concluded that stress test result announcements post financial crisis has a positive insignificant abnormal return before and on the day of announcements but negative insignificant abnormal returns after the announcements on DMBs return on stocks post financial crisis period in Nigeria.